2000
DOI: 10.1080/00288233.2000.9513409
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to low fertility hill country in New Zealand of white clover lines selected for differences in response to phosphorus

Abstract: White clover breeding lines developed as high and low P-responsive, in glasshouse selection trials, were compared, over three years, with 17 other breeding lines and cultivars for growth in four soil-fertility treatments under two defoliation treatments on a hill-country farm. Differences between P-response groups were transitory and biologically insignificant. Selection for differences in response to P in a controlled environment was not successful in identifying white clover germplasm adapted to low P hill-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
0
17
1
Order By: Relevance
“…In contrast 'Grasslands Tahora' surviving after 8 years did not retain the potential of the original seed line to respond to additional P, and behaved similarly to the resident material. The contribution of the P-responsive 'Huia' genotype to the total 'Huia' population is unknown but may be small, as other work has shown that fertiliser has little effect on the contribution that 'Huia' genotypes will make to the total white clover population (Hart 1986;Caradus & Dunn 2000;Hopkins et al 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast 'Grasslands Tahora' surviving after 8 years did not retain the potential of the original seed line to respond to additional P, and behaved similarly to the resident material. The contribution of the P-responsive 'Huia' genotype to the total 'Huia' population is unknown but may be small, as other work has shown that fertiliser has little effect on the contribution that 'Huia' genotypes will make to the total white clover population (Hart 1986;Caradus & Dunn 2000;Hopkins et al 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The two high-and low-phosphate responsive clover lines failed to demonstrate a competitive advantage over other lines in the field (experiment 1). Caradus & Dunn (2000) concluded that the selection for high-P response and low-P response populations of white clover in a controlled environment was not effective in producing lasting differences in growth in the field under contrasting P fertiliser additions. The weak significant source × fertiliser interaction and the non-significant trends, shown in experiment 1, demonstrates the high variability associated with the genetic differentiation of low-P sourced material doing better under low-P conditions than material sourced from high P. Germplasm that did achieve high growth under field conditions all had New Zealand parentage and medium to small leaf type morphology known to be well adapted to hill country (Williams & Caradus 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, testing for P use efficiency in the field can be problematic because of the often large spatial heterogeneity of P availability in the soil. In studies on white clover, P use efficiency was found to be heritable under glasshouse conditions, but this turned out not to be the case under field conditions (Caradus and Dunn 2000). On the other hand, successful selection for increased PUE was reported more recently for new soybean varieties, in this case by focussing on root architecture.…”
Section: Genetics and Breeding For Puementioning
confidence: 99%
“…Despite moderate heritability for responses to P application under controlled conditions (Caradus et al, 1992), white clover genotypes selected for improved phosphorus use efficiency (PUE) demonstrated no advantage under field conditions (Caradus, 1994;Caradus and Dunn, 2000), possibly due to a large genotype  environment interaction on the expression of PUE traits in the field. Therefore, root characteristics may be a more achievable target for improvement of white clover growth at low soil P levels.…”
Section: Selection For Root Traitsmentioning
confidence: 99%